Comparison of apical sealability of three obturation techniques (an in vitro study) (Mustansiria Dental Journal, 2018)
The aim of this study was to evaluate the sealing ability and the time required tocomplete obturationof three different obturation techniques.The palatal roots of sixtymaxillary first molar teeth were selectedfor this study. The root canals prepared usingProFile rotary instruments to an apical dimension of size 40 (.06 taper). Thespecimenswere then randomly divided into 3 experimental groups (20 sample of each) and filledwith gutta-percha and sealer byusing either cold lateral compaction, Thermafil, or theEasy & Quick Master system.For the first parameter(Time of obturation), the resultsshowed that Thermafil technique required the least time to complete obturation and itwas significantly lower than other twogroups.The second measurement(Microleakage) showed that the lateral condensation technique leaked apically andsignificantly higher than other test groups, while the Thermafil group exhibited theleast value of apical microleakage.